Comparison of Direct Surgical Costs for Proximal Row Carpectomy and Four-Corner Arthrodesis - Kazmers, Nikolas H.; Stephens, Andrew R.; Presson, Angela P.; Xu, Yizhe; Feller, Ross J.; Tyser, Andrew R. (Journal of Wrist Surgery, 2019)
Background Proximal row carpectomy (PRC) and four-corner arthrodesis (FCA) are common treatments for stage II scapholunate advanced collapse (SLAC) and scaphoid nonunion advanced collapse (SNAC) wrists, with similar functional and patient-reported outcomes reported in the peer-reviewed literature.Questions Study questions included (1) whether surgical encounter total direct costs (SETDCs) differ between PRC and FCA, and (2) whether SETDC differs by method of fixation for FCA.Patients and Methods Consecutive adult patients (≥ 18 years) undergoing PRC and FCA between July 2011 and May 2017 at a single tertiary care academic institution were identified. Patients undergoing additional simultaneous procedures were excluded. Using our institution's information technology value tools, we extracted prospectively collected cost data for each surgical encounter. SETDCs were compared between PRC and FCA, and between FCA subgroups (screws, plating, or staples).Results Of 42 included patients, mean age was similar between the 23 PRC and 19 FCA patients (51.2 vs. 54.5 years, respectively). SETDCs were significantly greater for FCA than PRC by 425%. FCA involved significantly greater facility costs (2.3-fold), supply costs (10-fold), and operative time (121 vs. 57 minutes). Implant costs were absent for PRC, which were responsible for 55% of the SETDC for FCA. Compared with compression screws, plating and staple fixation were significantly more costly (70% and 240% greater, respectively).Conclusion SETDCs were 425% greater for FCA than PRC. Implant costs for FCA alone were 130% greater than the entire surgical encounter for PRC. For FCA, SETDC varied depending on the method of fixation.Level of Evidence This is a level III, cost analysis study.
Keywords: cost; four-corner arthrodesis/fusion; proximal row carpectomy; scaphoidectomy; scapholunate advanced collapse wrist; scaphoid nonunion advanced collapse wrist; surgical encounter; value